Global Coalition for Africa (GCA) Meets in Cotonou, Benin June 9-11, 1993 - Dinka, Tesfaye (World Bank, Washington, DC, 2012)
The three-day meeting of the Global Coalition for Africa (GCA) which took place in Cotonou, Benin, June 9-11, 1993, was the occasion for discussion, debate, and recommendations on topics such as democratic governance, economic reforms, regional cooperation and integration, the population problem, HIV/AIDS, and the environment. The GCA representatives decided that the upcoming year would focus on the long-term themes of: developing indicators for measuring good governance; effective management of the twin processes of political and economic reform; and mobilization of resources with emphasis on domestic resources.